Profitabilitas Usaha Ternak Itik Petelur di Desa Kebonsari Kecamatan Candi, Sidoarjo - Budi, Eko Setyo; Yektiningsih, Endang; Priyanto, Eko (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
The aim of this research is to analyze the profitability of laying duck businesses and to analyze the feasibility of business laying duck in Kebonsari village, Candi Sub District, Sidoarjo, East Java. This research used descriptive qualitative approach and profitability analysis method. Primary data were collecting from 20 laying duck businesses in Kebonsari through interview and observation. The research result showed that the business profitability value of laying duck is 36.15% that was classified as low. That is the reason, why more than half of breeders were not continued this business. In business scale, about 1.500 laying duck, the breeders have to spend Rp102.6 million as fix cost per year and Rp22.5 million as variable cost per month. This business give the breeders Rp11.2 million per month as a profit.